Effect of different feed on nutritional content of black soldier fly (Hermetia illucens): A systematic review and meta-analysis - Lo, Diana; Loho, Luna; Afandi, Frendy Ahmad; Romulo, Andreas; Tedjakusuma, Felicia; Somma, Tammara; Kaburuan, Emil Robert; Zulkarnain, Arif; Khatri-Chhetri, Rupak (jurnal1, 2024)
Black Soldier Fly (Hermetia illucens) or BSF is commonly used in food industry as a meat substitute to reduce food waste and environmental pollution. It could grow effectively using organic material such as manure and food waste. In this study, a comparison of the nutritional content of BSF fed with manure and food waste will be determined by conducting a systematic review and meta-analysis. The information about protein, fat, carbohydrate, ash, and calcium content of manure or food waste fed BSF from various scientific database sources was analyzed and discussed. There were 720 literatures selected to be included in the meta-analysis dataset, with the main selection criteria: original research articles published in the last ten years with nutritional data on manure and food waste fed BSF. From the literature screening process, 8 articles were obtained and included in the meta-analysis. Based on meta-analysis, it was found that the food waste fed BSF group has approximately 16% higher protein content, 33% higher fat content, but 59% lower ash content if compared to manure fed BSF group. However, the use of food waste as BSF feed did not give a significant effect on BSF carbohydrate and calcium content when compared to manure fed BSF.